Investigation of plasmid profiles of enterococcus faecalis isolated from mastitic cow milks - Mehmet Öztürk; Süheyla Türkyılmaz (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study was to investigate the plasmid profiles of Enterococcus faecalis isolated from cow milk samples with mastitis. Materials and Methods: As a material, 54 E. faecalis strains isolated in the past years from milk samples with mastitis were used. Modified alkaline lysis method was used for plasmid isolation from bacteria. Results: Results revealed that 19 of isolates have plasmids varying one to eight and lengths of those were ranged approximately between 0.6 kb and 41 kb. It was determined that five isolates had only one plasmid while the other 14 had more plasmids. Following the plasmid isolation, cluster analysis was performed between the same and similar plasmids after their profile contends checked. Six clusters that containing two or more strains with similar plasmid profile were formed. Conclusions: Further studies should be designed to investigate the plasmids of other enterococci stains isolated from mastitis cow’s milks whether plasmids are responsible for antibiotic resistance.